Labour share developments over the past two decades The role of technological progress, globalisation and "winner-takes-most" dynamics - Schwellnus, Cyrille (OECD Economics Department Working Papers, 2018)
Over the past two decades, real median wage growth in many OECD countries has decoupled from labour productivity growth, partly reflecting declines in labour income shares. This paper analyses the drivers of labour share developments using a combination of industry- and firm-level data. Technological change in the investment goods-producing sector and greater global value chain participation have compressed labour shares, but the effect of technological change has been significantly less pronounced for high-skilled workers. Countries with falling labour shares have witnessed both a decline at the technological frontier and a reallocation of market shares toward "superstar" firms with low labour shares ("winner-takes-most" dynamics). The decline at the technological frontier mainly reflects the entry of firms with low labour shares into the frontier rather than a decline of labour shares in incumbent frontier firms, suggesting that thus far this process is mainly explained by technological dynamism rather than anti-competitive forces